Ikrar Talak dalam Perspektif Kompilasi Hukum Islam dan Fiqh Klasik: Analisis Komparatif - Melati Wulandari; Suwandono, Agus (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
This study explores the complexity of ikrar talak (divorce declaration) that does not comply with Indonesia's positive legal framework and its impact on the legal protection of wives and children. Although the Marriage Law and the Compilation of Islamic Law (KHI) regulate the formal procedures for divorce, verbal divorce declarations outside the court remain prevalent, causing legal uncertainty and harm to vulnerable parties. This research employs a normative juridical method, focusing on legal statutes and Islamic legal principles. The findings reveal the urgent need for harmonization between Islamic law and positive law to ensure justice and optimal protection, especially for women and children. Major obstacles include low legal literacy, social acceptance of verbal talak, and limited access to judicial institutions. The study proposes strengthening the role of religious courts, enhancing public legal education, and applying the maqashid sharia approach to safeguard fundamental rights. A holistic legal reform is necessary to ensure that the ikrar talak process adheres to formal legal standards while protecting vulnerable groups.